Biostratigraphy and Sequence Stratigraphy of Paleogene Deposits in Central Kopet-Dagh Basin (NE of Iran). (15th September 2013) - Rivandi, Batool; Vahidinia, Mohammad; Nadjafi, Mehdi; Mahboubi, Asadollah; Sadeghi, Abbas
Abstract : In this paper, the biostratigraphy and sequence stratigraphy of marine Paleogene deposits from the Kopet-Dagh basin (NE of Iran) are described. Particularly the absence of Morozovella genus is discussed. In addition, the Paleocene/Eocene boundary has been studied in detail using the record of planktonic and larger benthic foraminifera. This boundary is located probably within a thin red horizon (~10–15 cm) representing a paleosoil. Close to this boundary is located the base of the calcareous test dissolution interval, with the dominance of agglutinated benthic foraminifera and with a sudden decrease in the richness of benthic foraminiferal species. Biostratigraphic studies led to the identification of 33 genera of larger benthic foraminifera and 5 genera of planktonic foraminifera. Petrographical studies indicate that these sediments, consisting of four carbonate lithofacies (15 subfacies), may have been deposited on a shallow carbonate platform (ramp type). These lithofacies have been deposited in open marine, shoal, lagoon, and tidal flat environmental conditions. Sequence stratigraphic analysis led to the identification of four third-order depositional sequences. The interpreted sea-level curve in the Kopet-Dagh basin can be correlated with Paleocene-Eocene global curves, with a sea-level fall in the latest Paleocene, followed by a sea-level rise in the earliest Eocene.